2019
DOI: 10.1111/jcmm.14237
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin/ChemR23 axis promotes inflammation of glomerular endothelial cells in diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is characterized by inflammation of renal tissue. Glomerular endothelial cells (GEnCs) play an important role in inflammation and protein leakage in urine in DN patients. Chemerin and its receptor ChemR23 are inducers of inflammation. The aim of this study was to investigate the function of chemerin/ChemR23 in GEnCs of DN patients. Immunohistochemical staining and qRT‐PCR were used to measure the expression of chemerin, ChemR23 and inflammatory factors in renal tissues of DN patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 37 publications
1
36
1
1
Order By: Relevance
“…It has been reported that, in the kidney of diabetic animal model, the expression of CMKLR1 was gradually upregulated with the progression of renal dysfunction [35]. Knockdown of CMKLR1 ameliorated renal damage and inflammation in DN mice [36]. Recent studies showed that CMKLR1 was activated by Wnt/beta-catenin pathway which is involved in accumulation of extracellular matrix (ECM), podocyte dysfunction, and renal fibrosis in DN [3739].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, in the kidney of diabetic animal model, the expression of CMKLR1 was gradually upregulated with the progression of renal dysfunction [35]. Knockdown of CMKLR1 ameliorated renal damage and inflammation in DN mice [36]. Recent studies showed that CMKLR1 was activated by Wnt/beta-catenin pathway which is involved in accumulation of extracellular matrix (ECM), podocyte dysfunction, and renal fibrosis in DN [3739].…”
Section: Discussionmentioning
confidence: 99%
“…In human VSMCs, chemerin has pro-apoptotic, pro-inflammatory, and proliferative effects that are mediated by nicotinamide adenine dinucleotide phosphate oxidase (Nox) activation and redox-sensitive mitogen-activated protein kinases signalling [ 136 ]. In glomerular endothelial cells, chemerin treatment increases the secretion of the pro-inflammatory cytokines TNFα, IL-6, IL-8, and TGF-β1, and exposure to high concentrations of glucose increases the mRNA levels of both chemerin and CMKLR1 in these cells [ 137 ]. However, an anti-inflammatory effect of chemerin in endothelial cells by the inhibition of NF-κB, the TNF-α-induced adhesion of monocytes, and the oxidised low-density lipoprotein (oxLDL)-induced macrophage foam cell formation has also been described, as was a reduction in the presence of pro-inflammatory markers [ 86 , 113 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…Long-term exposure to HG levels induces glomerular endothelial cell inflammation and injury [7]. Different inflammatory molecules, including chemokines, adhesion molecules, and proinflammatory cytokines, are critical factors that may be involved in diabetic nephropathy [8].…”
Section: Introductionmentioning
confidence: 99%